Niech , tradycja jego działalności przetrwa wieki”. Popularyzacja i upowszechnianie dziedzictwa Karola Mikulego we Lwowie do 1939 roku - Fink, Kinga (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
The aim of this article is to retrace the presence of Karol Mikuli’s music and personality in the public space of Lviv at the turn of the 19th and 20th centuries. The analysis covered press sources – announcements, notes, reviews or reports on concerts and artistic events involving music – published in Lviv newspapers in the period after Mikuli’s death until 1939, covering both the years of Galician autonomy (1897–1918) and the period of the Second Polish Republic (1918–1939). In her search, the author found information about unknown events from Lviv’s musical life. They lead to a discussion about the date of birth of Chopin’s pupil, which remains a contentious issue to this day.